PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI TOKO SINAR BANGUNAN PALOPO - Ahmad Zakhi Afry; Suhardi M. Anwar; Tahier Ilham (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this research is to determine the influence of Compensation and Work Environment on Employee Performance at the Sinar Bangunan Palopo Store. This type of research is descriptive quantitative research. The sampling technique used a questionnaire with a Likert scale measurement scale. The population in this research were all employees of the Sinar Bangunan Palopo Store, totaling 67 people. The data processing used is the SPSS version 25 application. Based on the research results, it is proven that Compensation has a partial and significant effect on employee performance. Meanwhile, the Work Environment does not have a partial and significant effect on Employee Performance. Then Compensation and work environment have a simultaneous and significant effect on Employee Performance. To improve Employee Performance, especially in terms of cooperation, ability to complete work, etc., it is necessary to improve especially the Work Environment. The Work Environment must be improved in terms of workplace atmosphere, room temperature, etc. so that Employee Performance can improve.